Impementasi Media Pembelajaran Kantong Doraemon untuk Meningkatkan Kemampuan Numerasi Matematika Peserta Didik di Kelas I SDN Gemah - Kusuma, Afrisa Ardianty; Kusumaningsih, Widya; Widyastuti, Nora (ISLAMIKA, 2024)
Numeracy is a measuring skill in mathematics that involves reasoning skills so that it is necessary for daily life. To remind numeracy skills, you can use a method, namely by applying learning media. This research aims to improve the mathematical numeracy skills of grade 1 students of SDN Gemah Semarang City. This type of research uses quantitative research with a one-group pretest-posttest design. The operation of this study is all IA classes of SDN Gemah with a sampling technique using a nonprobability sampling technique with incidental sampling. The data used for evaluation is in the form of multiple-choice questions. Data analysis used normality test and paired sample t-test. The results of this study showed that the mathematical numeracy skills of grade 1 students could improve after being treated using Kantong Doraemon media. The results of the paired t-test, which is the average pretest of 69.67 and the average posttest of 83.00, the results of the analysis of the paired t-test with a significant correlation value of 0.01<0.05 can be stated that Ha is accepted. This shows that learning using Doraemon pocket media can improve students' numeracy skills. Based on the results of this study. It is recommended that teachers can apply various learning media to make students more active so that they can improve.